1998
DOI: 10.1074/jbc.273.30.18936
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transmembrane Movement of Newly Synthesized Phosphatidylethanolamine across the Inner Membrane of Escherichia coli

Abstract: Phospholipids are the major lipid component of the cell envelope of the Gram-negative bacterium Escherichia coli. Phospholipids are the only lipid constituent in the inner membrane and they build the inner leaflet of the outer membrane. The lipid matrix of the extracellular leaflet of the outer membrane consists of lipopolysaccharide (1, 2). The phospholipid content of the E. coli envelope comprises 75% phosphatidylethanolamine (PE), 1 which is a zwitterionic phospholipid, 20% phosphatidylglycerol, and 5% card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 54 publications
5
35
0
Order By: Relevance
“…Recent experiments designed to study phospholipid flip-flop in bacterial membranes and model liposomes have suggested that this process might be energy-independent in bacteria (58,59). In model membranes, lipid flip-flop occurs at near physiological rates in the absence of ATP or a proton motive force, provided that synthetic membrane-spanning peptides are reconstituted together with the lipids (60).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments designed to study phospholipid flip-flop in bacterial membranes and model liposomes have suggested that this process might be energy-independent in bacteria (58,59). In model membranes, lipid flip-flop occurs at near physiological rates in the absence of ATP or a proton motive force, provided that synthetic membrane-spanning peptides are reconstituted together with the lipids (60).…”
Section: Discussionmentioning
confidence: 99%
“…Why phospholipid transport to the outer membrane is blocked in msbA mutants is also unclear (143). There is evidence that phospholipid flip-flop is not ATP dependent in bacterial inner membrane vesicles (153). Although purified MsbA is a lipid-activated ATPase (154), phospholipid flip-flop could not be demonstrated in liposomes containing MsbA alone (155).…”
Section: Figurementioning
confidence: 99%
“…Indeed, all experimental studies that addressed this issue reported halftimes for transport of phospholipids in the order of minutes or less [12][13][14][15]. Biosynthesis and transport were found to be mechanistically not coupled and transport in-out was comparably rapid to transport out-in [13,16].…”
Section: Why Polyprenols As Lipid Anchors For the Peptidoglycan Units?mentioning
confidence: 99%